Change in the lymphocyte-to-monocyte ratio is an early surrogate marker of the efficacy of nivolumab monotherapy in advanced non-small-cell lung cancer. (October 2018) - Sekine, Katsutoshi; Kanda, Shintaro; Goto, Yasushi; Horinouchi, Hidehito; Fujiwara, Yutaka; Yamamoto, Noboru; Motoi, Noriko; Ohe, Yuichiro
Highlights: Nivolumab systemically activates the lymphocytes in NSCLC patients. Increase in Lymphocyte-to-monocyte ratio after nivolumab is related to prolonged PFS. Increase in Lymphocyte-to-monocyte ratio after docetaxel is not associated with PFS. Abstract: Objectives: Nivolumab, an anti-programmed cell death protein 1 (PD-1) monoclonal antibody, has been shown to yield a durable response and significant prolongation of the survival in some patients with non-small-cell lung cancer (NSCLC). However, identification of patients who are likely to respond to nivolumab remains difficult at present. Materials and methods: We conducted a retrospective analysis of the clinical data of 87 consecutive patients with advanced NSCLC seen in clinical practice who received nivolumab monotherapy at the National Cancer Center Hospital in Japan between January 2016 and July 2016 (discovery cohort). In addition, we also collected the clinical data of 75 patients who were administered nivolumab monotherapy between August 2016 and March 2017 (validation cohort). For this study, we focused on the changes in the lymphocyte-to-monocyte ratio (LMR) observed after nivolumab monotherapy. Results: In the discovery cohort, increase (≥10%) of the LMR at 4 weeks after the start of nivolumab monotherapy relative to the pretreatment LMR was positively correlated with an objective response (objective response rate (ORR); 39.4% vs 11.8%, p  = 0.0065). When this cutoff value of ≥10% was used, increase of the LMR was significantly associated with a prolonged progression-free survival (PFS) (median PFS [mPFS]; 7.3 months vs 2.5 months, p  = 0.0049) and overall survival (OS) (median survival time; 15.6 months vs 8.9 months, p  = 0.014). In the validation cohort also, increase of the LMR was significantly associated with higher ORR (50.0% vs 20.0%, p  = 0.015) and prolonged PFS (mPFS; not reached vs 3.1 months, p  = 0.0092). On the other hand, no such correlation was observed among patients treated with docetaxel. Conclusion: A rapid increase of the LMR was significantly associated with the effects of nivolumab monotherapy in our study cohort. Therefore, early change of the LMR may be used as a novel effective surrogate marker to decide on continuation of anti-PD-1 therapy.